Transforming superior teachers through the implementation of a prototype curriculum in the independent learning era - Rosnelli Rosnelli; Yuniarto Mudjisusatyo; Darwin Darwin (Jurnal Sinar Edukasi, 2025)
Teacher transformation is a key element in achieving the successful implementation of the Independent Curriculum in educational institutions. This article aims to analyze the role of the prototype curriculum implementation in shaping the profile of superior teachers who are adaptive, innovative, and oriented towards meaningful learning. This research uses a descriptive qualitative approach with data collection techniques through literature studies, observations of learning practices, and interviews with teachers implementing the Independent Curriculum in high schools in Deli Serdang Regency. The results show that the prototype curriculum encourages a paradigm shift in teachers from mere conveyors of material to facilitators of learning that foster student independence and creativity. Teachers also experience improvements in pedagogical competence, digital literacy, and the ability to design differentiated learning according to student characteristics. The implementation of this curriculum strengthens a reflective, collaborative, and sustainable spirit in teacher professional development. Thus, the implementation of the prototype curriculum not only updates the learning system but also becomes a catalyst for transformation towards superior teachers who are ready to face the challenges of education in the era of Independent Learning and Society 5.0.